TEACHER PERCEPTIONS AND IMPLEMENTATION OF A DEMOCRATIC CLASSROOM ATMOSPHERE IN ELEMENTARY SCHOOLS - Rahmadilla Putri Berliana; Wahdan Najib Habiby (Jurnal Cakrawala Pendas, 2024)
The implementation of a democratic classroom atmosphere in elementary schools is still very rare because most of them are still authoritarian and focus on the teacher, even though a democratic classroom atmosphere is very important because it can foster students' enthusiasm for learning, increase student participation in learning, teach democratic values, and create a classroom culture that reflects democratic character. Therefore, this research is important to find out the strategies and ways that teachers can create a democratic classroom atmosphere by recognizing the diverse characteristics of their students. Part of the purpose of this research is to find out teachers' understanding of a democratic classroom atmosphere, efforts, forms of implementation, and evaluations made by teachers in implementing a democratic classroom atmosphere in elementary schools. This study used a sample of 30 students from grades V and VI of SD Muhammadiyah 1 Ketelan Surakarta. This research is a type of descriptive qualitative research by describing the data that has been obtained and analyzing the results of the research. Data were collected through classroom observation, interviews, questionnaires, and documentation. Data analysis of research results using transcription and classification. The results in this study show that teachers have successfully implemented a democratic classroom atmosphere. Teacher perceptions are in accordance with the concept of a democratic classroom atmosphere, teacher efforts and implementation are carried out by fostering active participation of students in discussion activities, providing equal access and facilities, appreciation, interpreting diversity, and giving students freedom to express and speak without fear of being punished. Teacher evaluation uses reflection and direct observation during learning.